Influence Of Material Properties On The Aperture Filling During Stencil Printing Process - Mohamad Rafdzi, Muhammad Farid (Universiti Sains Malaysia, 2018)
High requirement of smaller size, lighter weight, and high performance Printed Circuit Board (PCB) in electronic packaging has contributed to the wide application of stencil printing for soldering process. Stencil printing offers good consistency of soldering performance as well as produce larger process output at short time that make it one of the best option for high volume application in Surface Mount Technology (SMT). However, the soldering method also contributes to major percentage of soldering defect compared to other methods which is necessary to be addressed through research and development. One of the common defects due to the stencil printing is regarding to the printing quality of solder paste on substrate such as PCB with respect to the variation of process parameters. Uncontrolled process parameters cause the soldering defects such as solder bridging that can lead to product failure in further processes in production line. An experiment has been conducted to analyse the influence of material properties on the aperture filling during solder printing process. The studied parameters are the printing speed, printing load and the printing direction. The study had found that the printing speed 35mm/s to 45mm/s has potential to obtain good print quality of solder filling. Printing load of 8kg to 9kg shows the good printing load option to achieve good print quality in stencil printing process. Finally, the reverse direction of printing mode shows a better quality compared to forward direction of printing mode.